LncRNA NNT-AS1 regulates proliferation, ECM accumulation and inflammation of human mesangial cells induced by high glucose through miR-214-5p/smad4 - Zhuang Geng (BMC, 2021)
Highlights 1. Up-regulated levels of NNT-AS1 and smad4 in DN samples and HGMCs was manifested. 2. Potential binding sites of NNT-AS1 showed miR-214-5p as its direct target and NNT-AS1 as potential absorber for this microRNA, in turn increasing the expression of transcription factor smad4. 3. The results manifested that knocking-down NNT-AS1 can significantly decrease the inflammation and progression of DN and hence can be used as a potential therapeutic target.